Prevalence and associated risk factors of abnormal pap smear in pregnant women - Mohindroo, Neha; Sharma, Anoop; Minhas, Santosh; Pathania, Kushla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The Papanicolaou test is a method of cervical screening used to detect pre-cancerous and cancerous processes. The incidence of cervical cancer in India is alarmingly high and is the leading cause of cancer in women in India accounting for 147 deaths per lakh women. Cervical cytological abnormalities are found in up to 5% of all pregnancies. In Indian settings, published data on abnormal Pap smear in pregnancy is lacking. The present study was designed to know the prevalence of abnormal Pap smear in pregnant women and its associated risk factors. Methods: This prospective study included 450 pregnant and 450 non-pregnant women who fulfilled the inclusion criteria. After a detailed history, clinical examination and investigations, Pap smear was collected as per conventional method and reported using 2014 Bethesda system. Results: 53.6% pregnant and 44.6% non-pregnant subjects had abnormal Pap smear. Out of the abnormal smears in pregnant women, 31.18% had inflammatory cytology, 15.37% had bacterial vaginosis, 4.01% had Trichomonal and 3.34% Monilial pathology. No epithelial cell abnormality was seen. Rural residence, lower class, age at first intercourse less than 21 years and having more than one sexual partner were important risk factors observed in our study and were statistically significant. Conclusions: Bacterial vaginosis, the most common infection detected on Pap smear is strongly associated with previos preterm labour and delivery. This opportunity for screening of cervical cancer and counselling should not be missed in the antenatal period.